Interpreting the General Letters : an exegetical handbook - Bateman, Herbert W., 1955-; Harvey, John D., 1951- (Grand Rapids, MI. Kregel Academic, 2013)
This handbook is designed as a step-by-step approach for analyzing and communicating eight letters of the New Testament: Hebrews, James, the Petrine Letters, the Johannine Letters, and Jude. Interpreting the General Letters provides important background material for these books' interpretation by exploring the types and component parts of letter writing, the importance of an amanuensis; the historical background of the Greco-Roman world, and implications of each of these factors for interpreting the general letters. --from publisher description
Preface -- Abbreviations -- The genre of the General Letters -- The background of the General Letters -- The theology of the General Letters -- Preparing to interpret the General Letters -- Interpreting passages in the General Letters -- Communicating the General Letters -- From exegesis to exposition of the General Letters -- Selected sources -- Glossary.
Includes bibliographical references.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Hermeneutics; Bible. -- Criticism, interpretation, etc; Bible. -- Hermeneutics